Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

High incidence of estrous cycle irregularities in heterogeneous stock (HS) rats is associated with footshock-resistant cocaine intake - Elizabeth A. Sneddon; Supakorn Chonwattanagul; Kathleen Bai; Pranav H. Kurup; Sonja L. Plasil; Michelle R. Doyle; Sélène Zahedi; Sierra Simpson; Benjamin C. Sichel; Dyar N. Othman; Molly Brennan; Abraham A. Palmer; et al. (Psychopharmacology, 2026)
Rationale Hormonal fluctuations throughout the estrous cycle are hypothesized to influence drug-related behaviors. Preclinical models show that some cocaine-related behaviors are influenced by the estrous cycle. However, the extent to which the estrous cycle modulates cocaine self-administration in outbred heterogeneous stock (HS) rats is unknown. Objectives We aimed to examine the relationship between estrous phases and cocaine self-administration behavior in HS rats using an operant model of extended access to cocaine self-administration. Methods We assessed the escalation of intake, breaking point, and resistance to foot shock. Using vaginal swabbing and lavage techniques, we characterized the relationship between estrous phase and cocaine behaviors. We then comprehensively evaluated estrous cycling patterns in young adult and adult HS rats, comparing them with Wistar rats. Results Estrous phase showed no association with cocaine self-administration in HS rats. 82% of female HS rats exhibited irregular estrous cycling with variability to the phase length, even in the absence of drug exposure, a phenomenon not observed in the Wistar strain. Females with irregular cycling showed greater footshock-resistant cocaine intake. Conclusions This study provides the first evidence that most female HS rats exhibit irregular estrous cycling. In HS rats, the estrous phase per se has no major influence on cocaine self-administration, whereas cycling irregularity was associated with specific addiction-related behaviors, including footshock-resistant intake. As HS rats gain popularity in behavioral and genome-wide studies, understanding these cycle disruptions is crucial as they may reveal genetic links into cycling variability and individual differences to aspects of cocaine use.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Ice-marginal volcanic sequence in Iceland found on a nondescript gradual hillslope: An unexpected record of ice thickness late in deglaciation - Audrey R. Putnam; Kirsten L. Siebach; Candice C. Bedford; Sarah L. Simpson; Michael T. Thorpe; Joseph J. Tamborski; Elizabeth B. Rampe (Journal of Volcanology and Geothermal Research, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Double dating sedimentary sequences using new applications of in-situ laser ablation analysis - Darwinaji Subarkah; Angus L. Nixon; Sarah E. Gilbert; Alan S. Collins; Morgan L. Blades; Alexander Simpson; Jarred C. Lloyd; Georgina M. Virgo; Juraj Farkaš (Lithos, 2024)

Association of physical function with connectivity in the sensorimotor and dorsal attention networks: why examining specific components of physical function matters - Madeline C. Boyd; Jonathan H. Burdette; Michael E. Miller; Robert G. Lyday; Christina E. Hugenschmidt; W. Jack Rejeski; Sean L. Simpson; Laura D. Baker; Chal E. Tomlinson; Stephen B. Kritchevsky; Paul J. Laurienti (GeroScience, 2024)
Declining physical function with aging is associated with structural and functional brain network organization. Gaining a greater understanding of network associations may be useful for targeting interventions that are designed to slow or prevent such decline. Our previous work demonstrated that the Short Physical Performance Battery (eSPPB) score and body mass index (BMI) exhibited a statistical interaction in their associations with connectivity in the sensorimotor cortex (SMN) and the dorsal attention network (DAN). The current study examined if components of the eSPPB have unique associations with these brain networks. Functional magnetic resonance imaging was performed on 192 participants in the BNET study, a longitudinal and observational trial of community-dwelling adults aged 70 or older. Functional brain networks were generated for resting state and during a motor imagery task. Regression analyses were performed between eSPPB component scores (gait speed, complex gait speed, static balance, and lower extremity strength) and BMI with SMN and DAN connectivity. Gait speed, complex gait speed, and lower extremity strength significantly interacted with BMI in their association with SMN at rest. Gait speed and complex gait speed were interacted with BMI in the DAN at rest while complex gait speed, static balance, and lower extremity strength interacted with BMI in the DAN during motor imagery. Results demonstrate that different components of physical function, such as balance or gait speed and BMI, are associated with unique aspects of brain network organization. Gaining a greater mechanistic understanding of the associations between low physical function, body mass, and brain physiology may lead to the development of treatments that not only target specific physical function limitations but also specific brain networks.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

Stressful life events and depression and fatigue in people with multiple sclerosis: a cross-sectional analysis of an international cohort - Jeanette C. Reece; Sandra L. Neate; Rebekah A. Davenport; Elasma Milanzi; Nupur Nag; William Bevens; Maggie Yu; George A. Jelinek; Steve Simpson-Yap (Acta Neurologica Belgica, 2024)
Background Relationships between stressful life events (SLEs) and health outcomes in people living with multiple sclerosis (plwMS), beyond relapse, are not well-established. We examined associations between SLEs and fatigue and symptoms of depression in plwMS. Methods 948 participants were queried whether they had experienced any of the 16 SLEs (Holmes–Rahe Social Readjustment Rating Scale) in the preceding 12 months. SLEs were summated to estimate SLE number and SLE load (weighted for the degree of associated stress). Cross-sectional associations between SLE (number, load and individual) and fatigue, and depressive symptoms were examined using log-binomial or log-multinomial regression adjusted for age, sex, relapse symptoms, education, MS type at baseline, disability, fatigue, comorbidity, depression, and antidepressant/antifatigue medications, as appropriate. Sub-analyses restricted to SLEs with a negative emotional impact were performed. Results Median SLE number and load were 2 (IQR 1–2) and 57 (IQR 28–97), respectively. SLE number and load were not associated with a higher prevalence of fatigue, or depressive symptoms, even when restricting analyses to SLEs with a perceived negative emotional impact. A new relationship or family member with a negative impact was associated with a threefold and 2.5-fold higher prevalence of depressive symptoms, respectively. Serious illness was associated with a 28% higher prevalence of depressive symptoms. Conclusion Psychological support for SLEs, and/or intervention targeted to SLE appraisal, may be beneficial in mitigating the adverse effects of SLEs with a perceived negative emotional impact on depressive symptoms in plwMS. Potential associations between serious illness and increased prevalence of depressive symptoms may warrant further investigation.

Integrated Exposure–Response of Dupilumab in Children, Adolescents, and Adults With Atopic Dermatitis Using Categorical and Continuous Efficacy Assessments: A Population Analysis - Emily Briggs; Mohamed A. Kamal; Matthew P. Kosloski; Ian Linsmeier; Natalie Jusko; Nancy Dolphin; Jason Chittenden; Eric L. Simpson; Amy S. Paller; Elaine C. Siegfried; Brad Shumel; Noah A. Levit; et al. (Pharmaceutical Research, 2023)
Background While the majority of patients with atopic dermatitis (AD) achieve disease control with dupilumab treatment, there is variability in which patients achieve clear disease. The predictors of these responses are currently unclear. Integrated models were developed to evaluate the exposure–response (E-R) relationship of dupilumab in children, adolescents, and adults with AD. Methods Data from six Phase II and III clinical studies were pooled (2,366 adults [> 18 years], 243 adolescents [≥ 12 to < 18 years] and 359 children [≥ 6 to < 12 years]) for model development. Efficacy was assessed using the Eczema Area and Severity Index (EASI) and Investigator’s Global Assessment (IGA). Indirect response models were applied to link measures of efficacy and functional serum dupilumab concentrations. The covariates on individual placebo-corrected response were assessed. Clinical trial scenarios were simulated to compare E-R relationships across age groups. Safety was not explored. Results After correcting for differences in placebo response and dupilumab exposure: 1) older age, higher body weight, lower baseline thymus and activation-regulated chemokine, and Asian race were associated with slightly lower EASI response, and no clear covariates were identified on IGA response; 2) clinical trial simulations generally showed slightly higher response at a given dupilumab concentration in children compared to adults and adolescents with severe and moderate AD. Conclusions The collectively tested covariates explain some of the variability in dupilumab response in patients with AD. Patients in all age groups showed adequate response to dupilumab; however, children showed slightly higher drug effects compared to adults and adolescents at equivalent concentrations.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency - Shabnam Bakhshalizadeh; Daniella H. Hock; Nicole A. Siddall; Brianna L. Kline; Rajini Sreenivasan; Katrina M. Bell; Franca Casagranda; Sadishkumar Kamalanathan; Jayaprakash Sahoo; Niya Narayanan; Dukhabandhu Naik; Varun Suryadevara; et al. (Human Genetics, 2023)
Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp) shared by twin sisters presenting with POI, bilateral high-frequency sensorineural hearing loss, kidney and heart dysfunction. MRPL50 encodes a component of the large subunit of the mitochondrial ribosome. Using quantitative proteomics and western blot analysis on patient fibroblasts, we demonstrated a loss of MRPL50 protein and an associated destabilisation of the large subunit of the mitochondrial ribosome whilst the small subunit was preserved. The mitochondrial ribosome is responsible for the translation of subunits of the mitochondrial oxidative phosphorylation machinery, and we found patient fibroblasts have a mild but significant decrease in the abundance of mitochondrial complex I. These data support a biochemical phenotype associated with MRPL50 variants. We validated the association of MRPL50 with the clinical phenotype by knockdown/knockout of mRpL50 in Drosophila , which resulted abnormal ovarian development. In conclusion, we have shown that a MRPL50 missense variant destabilises the mitochondrial ribosome, leading to oxidative phosphorylation deficiency and syndromic POI, highlighting the importance of mitochondrial support in ovarian development and function.

Venom phenotype conservation suggests integrated specialization in a lizard-eating snake - Tucker C. Heptinstall; Jason L. Strickland; Ramses A. Rosales-Garcia; Rhett M. Rautsaw; Cassandra L. Simpson; Gunnar S. Nystrom; Schyler A. Ellsworth; Michael P. Hogan; Miguel Borja; Pollyanna Fernandes Campos; Felipe G. Grazziotin; Darin R. Rokyta; et al. (Toxicon, 2023)

Diphenhydramine-Induced Antimuscarinic Delirium Treated with Physostigmine and Transdermal Rivastigmine - James D. Whitledge; C. James Watson; Michael Simpson; Azza Bakkar; Leora Boussi; Michael Scott; Katherine L. Boyle (Journal of Medical Toxicology, 2023)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantification and Degradation of 2,2-Dibromo-3-Nitrilopropionamide (DBNPA) in Bioethanol Fermentation Coproducts - J. V. Simpson; C. L. Wiatr (World Journal of Microbiology and Biotechnology, 2022)
2,2-Dibromo-3-nitrilopropionamide (DBNPA) has been used as a biocide in industrial water applications due to its instantaneous antimicrobial activity and rapid chemical breakdown. In this study, DBNPA is considered a potential alternative for antibiotics used for bacterial control during corn-to-ethanol fermentation. A method using LC/MS/MS was developed to accurately quantify DBNPA in water. When this method was applied to quantify DBNPA concentration in a fermentation matrix, DBNPA was found to be unstable and to decay rapidly, preventing validation of the method or quantitation. This method was then used to evaluate the degradation rate of DBNPA in whole stillage, which is the nonvolatile residue produced by removal of ethanol from corn-based fermentation beer by distillation through the relative decrease in measured signal. In addition, a method was developed and validated to quantify bromide, one of the degradation products of DBNPA, in whole stillage using LC/MS/MS. The degradation rate of DBNPA in whole stillage was found to display first-order kinetics with a calculated half-life of 85 min. Laboratory analytical chemistry results on DBNPA degradation were confirmed based on a bacterial viability assay in field trials.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Bird rookery nutrient over-enrichment as a potential accelerant of mangrove cay decline in Belize - L. T. Simpson; S. W. J. Canty; J. R. Cissell; M. K. Steinberg; J. A. Cherry; I. C. Feller (Oecologia, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Lung abnormalities do not influence aerobic capacity in school children born preterm - Christopher A. O’Dea; Karla Logie; Andrew C. Wilson; J. Jane Pillow; Conor Murray; Georgia Banton; Shannon J. Simpson; Graham L. Hall; Andrew Maiorana (European Journal of Applied Physiology, 2021)

Bayesian Inverse Transient Analysis for Pipeline Condition Assessment: Parameter Estimation and Uncertainty Quantification - Chi Zhang; Martin F. Lambert; Jinzhe Gong; Aaron C. Zecchin; Angus R. Simpson; Mark L. Stephens (Water Resources Management, 2020)

Quantifying Soft Tissue Artefacts and Imaging Variability in Motion Capture of the Fingers - C. D. Metcalf; C. Phillips; A. Forrester; J. Glodowski; K. Simpson; C. Everitt; A. Darekar; L. King; D. Warwick; A. S. Dickinson (Annals of Biomedical Engineering, 2020)
This study assessed the accuracy of marker-based kinematic analysis of the fingers, considering soft tissue artefacts (STA) and marker imaging uncertainty. We collected CT images of the hand from healthy volunteers with fingers in full extension, mid- and full-flexion, including motion capture markers. Bones and markers were segmented and meshed. The bone meshes for each volunteer’s scans were aligned using the proximal phalanx to study the proximal interphalangeal joint (PIP), and using the middle phalanx to study the distal interphalangeal joint (DIP). The angle changes between positions were extracted. The HAWK protocol was used to calculate PIP and DIP joint flexion angles in each position based on the marker centroids. Finally the marker locations were ‘corrected’ relative to the underlying bones, and the flexion angles recalculated. Static and dynamic marker imaging uncertainty was evaluated using a wand. A strong positive correlation was observed between marker- and CT-based joint angle changes with 0.980 and 0.892 regression slopes for PIP and DIP, respectively, and Root Mean Squared Errors below 4°. Notably for the PIP joint, correlation was worsened by STA correction. The 95% imaging uncertainty interval was

Mangroves dramatically increase carbon storage after 3 years of encroachment - L. T. Simpson; C. M. Stein; T. Z. Osborne; I. C. Feller (Hydrobiologia, 2019)

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Regional variability in the atmospheric nitrogen deposition signal and its transfer to the sediment record in Greenland lakes - N. J. Anderson; C. J. Curtis; E. J. Whiteford; V. J. Jones; S. McGowan; G. L. Simpson; J. Kaiser (Limnology and Oceanography, 2018)
Disruption of the nitrogen cycle is a major component of global environmental change. δ 15 N in lake sediments is increasingly used as a measure of reactive nitrogen input but problematically, the characteristic depleted δ 15 N signal is not recorded at all sites. We used a regionally replicated sampling strategy along a precipitation and N‐deposition gradient in SW Greenland to assess the factors determining the strength of δ 15 N signal in lake sediment cores. Analyses of snowpack N and δ 15 N‐NO 3 and water chemistry were coupled with bulk sediment δ 15 N. Study sites cover a gradient of snowpack δ 15 N (ice sheet: −6‰; coast 10‰), atmospheric N deposition (ice sheet margin: ∼ 0.2 kg ha −1 yr −1 ; coast: 0.4 kg ha −1 yr −1 ) and limnology. Three 210 Pb‐dated sediment cores from coastal lakes showed a decline in δ 15 N of ca. 1‰ from ∼ 1860, reflecting the strongly depleted δ 15 N of snowpack N, lower in‐lake total N (TN) concentration (∼ 300 μ g N L −1 ) and a higher TN‐load. Coastal lakes have 3.7–7.1× more snowpack input of nitrate than inland sites, while for total deposition the values are 1.7–3.6× greater for lake and whole catchment deposition. At inland sites and lakes close to the ice‐sheet margin, a lower atmospheric N deposition rate and larger in‐lake TN pool resulted in greater reliance on N‐fixation and recycling (mean sediment δ 15 N is 0.5–2.5‰ in most inland lakes; n = 6). The primary control of the transfer of the atmospheric δ 15 N deposition signal to lake sediments is the magnitude of external N inputs relative to the in‐lake N‐pool.

Environmental exposure and parental collection does not affect detection or semi-quantitative load assessment of bacteria in nasal swab specimens from children - Nada Townsi; Shannon J. Simpson; Chisha T. Sikazwe; Glenys R. Chidlow; Graham L. Hall; J. Jane Pillow; Andrew C. Wilson; David W. Smith; Ingrid A. Laing (Infectious Diseases, 2018)

Effects of sprint interval training on ectopic lipids and tissue-specific insulin sensitivity in men with non-alcoholic fatty liver disease - Jack A. Sargeant; Stephen Bawden; Guruprasad P. Aithal; Elizabeth J. Simpson; Ian A. Macdonald; Mark C. Turner; Jessica Cegielski; Kenneth Smith; James L. Dorling; Penny A. Gowland; Myra A. Nimmo; James A. King (European Journal of Applied Physiology, 2018)

A cross correlation method for chemical profiles in minerals, with an application to zircons of the Kilgore Tuff (USA) - L. C. Probst; T. E. Sheldrake; M. J. Gander; G. Wallace; G. Simpson; L. Caricchi (Contributions to Mineralogy and Petrology, 2018)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Scientific Considerations for the Assessment and Management of Mine Tailings Disposal in the Deep Sea - Lindsay L. Vare; Maria C. Baker; John A. Howe; Lisa A. Levin; Carlos Neira; Eva Z. Ramirez-Llodra; Amanda Reichelt-Brushett; Ashley A. Rowden; Tracy M. Shimmield; Stuart L. Simpson; Eulogio H. Soto (Frontiers in Marine Science, 2018)

Carbon Storages along a Climate Induced Coastal Wetland Gradient - L. T. Simpson; T. Z. Osborne; L. J. Duckett; I. C. Feller (Wetlands, 2017)

Duration of fascicle shortening is affected by muscle architecture and sex - C. L. Simpson; S. Arefin; R. R. Smart; B. Harwood; Jennifer M. Jakobi (European Journal of Applied Physiology, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Long-term efavirenz use is associated with worse neurocognitive functioning in HIV-infected patients - Qing Ma; Florin Vaida; Jenna Wong; Chelsea A. Sanders; Yu-ting Kao; David Croteau; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; Justin C. McArthur; Susan Morgello; et al. (Journal of NeuroVirology, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

Marine extinction risk shaped by trait–environment interactions over 500 million years - Emily A. Orzechowski; Rowan Lockwood; Jarrett E. K. Byrnes; Sean C. Anderson; Seth Finnegan; Zoe V. Finkel; Paul G. Harnik; David R. Lindberg; Lee Hsiang Liow; Heike K. Lotze; Craig R. McClain; Jenny L. McGuire; et al. (Global Change Biology, 2015)
Perhaps the most pressing issue in predicting biotic responses to present and future global change is understanding how environmental factors shape the relationship between ecological traits and extinction risk. The fossil record provides millions of years of insight into how extinction selectivity (i.e., differential extinction risk) is shaped by interactions between ecological traits and environmental conditions. Numerous paleontological studies have examined trait‐based extinction selectivity; however, the extent to which these patterns are shaped by environmental conditions is poorly understood due to a lack of quantitative synthesis across studies. We conducted a meta‐analysis of published studies on fossil marine bivalves and gastropods that span 458 million years to uncover how global environmental and geochemical changes covary with trait‐based extinction selectivity. We focused on geographic range size and life habit (i.e., infaunal vs. epifaunal), two of the most important and commonly examined predictors of extinction selectivity. We used geochemical proxies related to global climate, as well as indicators of ocean acidification, to infer average global environmental conditions. Life‐habit selectivity is weakly dependent on environmental conditions, with infaunal species relatively buffered from extinction during warmer climate states. In contrast, the odds of taxa with broad geographic ranges surviving an extinction (>2500 km for genera, >500 km for species) are on average three times greater than narrow‐ranging taxa (estimate of odds ratio: 2.8, 95% confidence interval = 2.3–3.5), regardless of the prevailing global environmental conditions. The environmental independence of geographic range size extinction selectivity emphasizes the critical role of geographic range size in setting conservation priorities.

Fitness level impacts salivary antimicrobial protein responses to a single bout of cycling exercise - Hawley Kunz; Nicolette C. Bishop; Guillaume Spielmann; Mira Pistillo; Justin Reed; Teja Ograjsek; Yoonjung Park; Satish K. Mehta; Duane L. Pierson; Richard J. Simpson (European Journal of Applied Physiology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Long-term copper partitioning of metal-spiked sediments used in outdoor mesocosms - Stephanie Gardham; Grant C. Hose; Stuart L. Simpson; Chad Jarolimek; Anthony A. Chariton (Environmental Science and Pollution Research, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Prevalence of polypharmacy in a Scottish primary care population - R. A. Payne; A. J. Avery; M. Duerden; C. L. Saunders; C. R. Simpson; G. A. Abel (European Journal of Clinical Pharmacology, 2014)

Lasting neurobehavioral abnormalities in rats after neonatal activation of serotonin 1A and 1B receptors: possible mechanisms for serotonin dysfunction in autistic spectrum disorders - Nidhi Khatri; Kimberly L. Simpson; Rick C. S. Lin; Ian A. Paul (Psychopharmacology, 2014)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Associations of whole-blood fatty acids and dietary intakes with prostate cancer in Jamaica - Maria D. Jackson; Susan P. Walker; Candace M. Simpson-Smith; Carole M. Lindsay; Garret Smith; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2012)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

An Integrated Approach to Gene Discovery and Marker Development in Atlantic Cod (Gadus morhua) - Sharen Bowman; Sophie Hubert; Brent Higgins; Cynthia Stone; Jennifer Kimball; Tudor Borza; Jillian Tarrant Bussey; Gary Simpson; Catherine Kozera; Bruce A. Curtis; Jennifer R. Hall; Tiago S. Hori; et al. (Marine Biotechnology, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Vegetative reproduction facilitates early expansion of Phyla canescens in a semi-arid floodplain - J. N. Price; M. J. Macdonald; C. L. Gross; R. D. B. Whalley; I. H. Simpson (Biological Invasions, 2011)

Body size and risk of prostate cancer in Jamaican men - Maria D. Jackson; Susan P. Walker; Candace M. Simpson; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2010)

Toxicity of Metals to the Bivalve Tellina deltoidalis and Relationships Between Metal Bioaccumulation and Metal Partitioning Between Seawater and Marine Sediments - C. K. King; M. C. Dowse; S. L. Simpson (Archives of Environmental Contamination and Toxicology, 2010)

Paleolimnological evidence of the effects on lakes of energy and mass transfer from climate and humans - Peter R. Leavitt; S. C. Fritz; N. J. Anderson; P. A. Baker; T. Blenckner; L. Bunting; J. Catalan; D. J. Conley; W. O. Hobbs; E. Jeppesen; A. Korhola; S. McGowan; et al. (Limnology and Oceanography, 2009)
The premise of this article is that climate effects on lakes can be quantified most effectively by the integration of process‐oriented limnological studies with paleolimnological research, particularly when both disciplines operate within a common conceptual framework. To this end, the energy (E)‐mass ( m ) flux framework (E m flux) is developed and applied to selected retrospective studies to demonstrate that climate variability regulates lake structure and function over diverse temporal and spatial scales through four main pathways: rapid direct transfer of E to the lake surface by irradiance, heat, and wind; slow indirect effects of E via changes in terrestrial development and subsequent m subsidies to lakes; direct influx of m as precipitation, particles, and solutes from the atmosphere; and indirect influx of water, suspended particles, and dissolved substances from the catchment. Sedimentary analyses are used to illustrate the unique effects of each pathway on lakes but suggest that interactions among mechanisms are complex and depend on the landscape position of lakes, catchment characteristics, the range of temporal variation of individual pathways, ontogenetic changes in lake basins, and the selective effects of humans on m transfers. In particular, preliminary synthesis suggests that m influx can overwhelm the direct effects of E transfer to lakes, especially when anthropogenic activities alter m subsidies from catchments.

Toward increasing avian diversity: urban wildscapes programs - Amanda L. Aurora; Thomas R. Simpson; Michael F. Small; Kelly C. Bender (Urban Ecosystems, 2009)

Urban geochemistry: research strategies to assist risk assessment and remediation of brownfield sites in urban areas - I. Thornton; M. E. Farago; C. R. Thums; R. R. Parrish; R. A. R. McGill; N. Breward; N. J. Fortey; P. Simpson; S. D. Young; A. M. Tye; N. M. J. Crout; R. L. Hough; et al. (Environmental Geochemistry and Health, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Use of life history information in a population model for Sacramento green sturgeon - Raymond C. P. Beamesderfer; Michele L. Simpson; Gabriel J. Kopp (Environmental Biology of Fishes, 2007)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)

A note on the relationship between temperature and water vapor over oceans, including sea surface temperature effects - C. -L. Shie; W. -K. Tao; J. Simpson (Advances in Atmospheric Sciences, 2006)

An Assessment of Five Australian Polychaetes and Bivalves for Use in Whole-Sediment Toxicity Tests: Toxicity and Accumulation of Copper and Zinc from Water and Sediment - C. K. King; M. C. Dowse; S. L. Simpson; D. F. Jolley (Archives of Environmental Contamination and Toxicology, 2004)

Effects of administration of somatostatin‐14 and immunoneutralization of somatostatin on endocrine and growth responses in rainbow trout - B. C. Peterson; P. R. Simpson; K. D. Cain; R. H. Hardy; G. T. Schelling; T. L. Ott (Journal of Fish Biology, 2003)
Injection of somatostatin‐14 (SS‐14) at 5 ng g −1 body mass (BM) into rainbow trout Oncorhynchus mykiss decreased ( P r 2 = 0·54) levels of growth hormone (GH) (1·5 ± 0·9 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time when compared to controls. Somatostatin‐14 at 50 ng g −1 BM also decreased ( P = 0·064, q uadratic; r 2 = 0·30) levels of GH (3·6 ± 2·1 ng ml −1 v. 6·6 ± 0·6 ng ml −1 ) over time compared to controls. In a second study, passive immunization against SS‐14 (1 : 25 dose) increased ( P = 0·10, cubic, r 2 = 0·12) levels of GH (11·0 ± 4·8 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time. Passively immunizing against SS‐14 (1 : 50 dose) increased ( P r 2 = 0·10) levels of GH (8·2 ± 2·3 ng ml −1 v. 5·2 ± 1·4 ng ml −1 ) over time compared to controls. Overall, in the active immunization study there was no difference ( P > 0·10) in specific growth rate ( G ) or feed conversion ratio ( FCR ) between the three treatment groups during the 9 weeks of the study. Only four of the fish immunized against SS‐14, however, developed antibody titres against SS. Compared to controls, these fish exhibited a G of 0·89 ± 0·09 v. 0·56 ± 0·09% per 3 weeks and FCR of 0·80 ± 0·04 v. 1·20 ± 0·05 g g −1 . In SS‐14 immunized fish, levels of GH decreased ( P P G and FCR is dependent upon generation of antibody titres.

Microphysics, radiation and surface processes in the Goddard Cumulus Ensemble (GCE) model - Wei-Kuo Tao; J. Simpson; D. Baker; S. Braun; M.-D. Chou; B. Ferrier; D. Johnson; A. Khain; S. Lang; B. Lynn; C.-L. Shie; D. Starr; et al. (Meteorology and Atmospheric Physics, 2003)

Coherence between one random and one periodic signal for measuring the strength of responses in the electro-encephalogram during sensory stimulation - A. M. F. L. Miranda de Sá; A. F. C. Infantosi; D. M. Simpson (Medical & Biological Engineering & Computing, 2002)

Plankton dynamics: observed and modelled responses to physical conditions in Prince William Sound, Alaska - David L. Eslinger; R. Ted Cooney; C. Peter Mcroy; Alison Ward; Thomas C. Kline; E. Paul Simpson; Jia Wang; Jennifer R. Allen (Fisheries Oceanography, 2001)
Plankton populations in Prince William Sound, Alaska, exhibited pronounced seasonal, annual and longer‐period variability in composition and standing stock in response to physically influenced differences in nutrient availability, and possibly currents that modify local biomass by exchanges with water from the bordering Gulf of Alaska. During springs in which early, strong physical stratification developed, intense, short‐lived phytoplankton blooms occurred. These blooms had relatively short residence times in the water column. In contrast, during springs in which slower, weaker stratification developed, phytoplankton blooms were prolonged and took longer to peak. These slower blooms prolonged the period of phytoplankton production, prolonged interaction with the springtime grazing community and led to the incorporation of more organic matter into pelagic food webs. A coupled biological‐physical simulation of plankton production was used to examine the implications of seasonally varying air and mixed‐layer temperatures, surface winds and incident light on the timing, duration, annual production and standing stock of plankton. Our modelling results reproduced the observed characteristics of the springtime production cycle, and the magnitude of zooplankton stocks for the period 1992–97 but not for 1981–91. These results suggest that for most of the 1990s, bottom‐up influences on nutrient supplies controlled levels of primary consumers, whereas for the 11 years before that, other unknown factors dominated this process. We present the results of a comprehensive, multiyear study of relationships between plankton and physical limitations, and a retrospective analysis of earlier conditions to explore the possible causes for these differences.

Aircraft Measurements of Dimethyl Sulfide (DMS) Using a Whole Air Sampling Technique - I. J. Simpson; J. J. Colman; A. L. Swanson; A. R. Bandy; D. C. Thornton; D. R. Blake; F. S. Rowland (Journal of Atmospheric Chemistry, 2001)

Somaclonal variation in cryopreserved embryogenic clones of white spruce [ Picea glauca (Moench) Voss.] - L. L. DeVerno; Y. S. Park; J. M. Bonga; J. D. Barrett; C. Simpson (Plant Cell Reports, 1999)

Genomic organisation of the human chordin gene and mutation screening of candidate Cornelia de Lange syndrome genes - M. Smith; S. Herrell; M. Lusher; L. Lako; C. Simpson; A. Wiestner; R. Skoda; M. Ireland; T. Strachan (Human Genetics, 1999)

Genomic organisation of the human chordin gene and mutation screening of candidate Cornelia de Lange syndrome genes - M. Smith; S. Herrell; M. Lusher; L. Lako; C. Simpson; A. Wiestner; R. Skoda; M. Ireland; T. Strachan (Human Genetics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

An investigation of the temporal induction of cytokine mRNAs in LPS-challenged thioglycollate-elicited murine peritoneal macrophages using the reverse transcription polymerase chain reaction - A. E. C. M. Simpson; P. T. Tomkins; K. L. Cooper (Inflammation Research, 1997)